Epidemiological study of a large cluster of fungaemia cases due to Kodamaea ohmeri in an Indian tertiary care centre. (4th September 2013) - Chakrabarti, A.; Rudramurthy, S. M.; Kale, P.; Hariprasath, P.; Dhaliwal, M.; Singhi, S.; Rao, K. L. N.; Roilides, E.
Abstract While performing molecular confirmation of phenotypically identified Candida tropicalis isolates, we re‐identified a few isolates as Kodamaea ohmeri. This led us to the present epidemiological investigation of K. ohmeri fungaemia cases. All phenotypically identified C. tropicalis blood isolates during October 2008 through to December 2009 at our advanced paediatric centre were included for molecular identification by sequencing of the internal transcribed spacer and D1/D2 regions of rDNA. After identifying a large cluster K. ohmeri fungaemia cases, a case–control study was carried out retrospectively to analyse potential risk factors for K. ohmeri fungaemia. Molecular typing of the isolates was performed using a fluorescent amplified fragment length polymorphism (FAFLP) technique. The antifungal susceptibility testing was performed as per the M27‐A3 protocol of CLSI. Thirty‐eight (25.7%) of 148 phenotypically identified C. tropicalis isolates were confirmed as K. ohmeri by sequencing and FAFLP. By case–control analysis, piperacillin‐tazobactam was significantly associated with the K. ohmeri fungaemia. The FAFLP analysis showed that all K. ohmeri isolates had >92% similarity. The azoles and echinocandins had good in vitro activity against K. ohmeri, though 86.8% of the isolates had MIC of 1 mg/L for amphotericin B. The response to antifungal therapy could be evaluated in 27 patients and 70.4% of patients recovered after antifungal therapy. The present study reports the largest cluster of K. ohmeri fungaemia from a single centre. The study also stresses the need for accurate identification of clinical yeast isolates.